How Does Financial Globalization Affect Risk Sharing? : Patterns and Channels - Terrones, Marco (IMF Working Papers; Working Paper ;, 2007)
In theory, one of the main benefits of financial globalization is that it should allow for more efficient international risk sharing. This paper provides a comprehensive empirical evaluation of the patterns of risk sharing among different groups of countries and examines how international financial integration has affected the evolution of these patterns. Using a variety of empirical techniques, we conclude that there is at best a modest degree of international risk sharing, and certainly nowhere near the levels predicted by theory. In addition, only industrial countries have attained better risk sharing outcomes during the recent period of globalization. Developing countries have, by and large, been shut out of this benefit. The most interesting result is that even emerging market economies, which have experienced large increases in cross-border capital flows, have seen little change in their ability to share risk. We find that the composition of flows may help explain why emerging markets have not been able to realize this presumed benefit of financial globalization. In particular, our results suggest that portfolio debt, which has dominated the external liability stocks of most emerging markets until recently, is not conducive to risk sharing.